BOOTCAMP PROKLIM SEBAGAI METODE PEMBINAAN PROKLIM DI TINGKAT DUSUN - Alvan, Eri Nur; Khoiruumah, Ilma; Nurariyanti, Elsa; Karwati, Lilis; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Proklim coaching has not been productive, socialization is often held but only in recitation or only with hamlet heads, it is not in accordance with the program, so intensive mentoring efforts are needed so that the Proklim program can run. The aim of the Proklim bootcamp program is to disseminate information, form habits for movement. or the form of implementation of the Climate Village Program, qualitative descriptive method. The techniques used are lectures and question and answer discussions. Results of activities targeting the Sukajaya Hamlet, Cikujang Be'et Hamlet and Cidangiang Hamlet areas. The material presented at this socialization concerns 3 aspects of climate change, namely adaptation, mitigation and institutions. The Proklim Bootcamp consists of four stages. The first is the preparation stage, the second stage is innovation, the third stage is catalysis, and the evaluation stage. In the planning stage the aim is to build a strong understanding of the issue of climate change and the importance of participating in mitigation and adaptation efforts to the current weather. Then in the innovation process, the Proklim Facilitator explores the potential and problems. In the catalyzing stage of implementation of the blueprint. Finally, the blueprint evaluation process has been implemented successfully and achieved the desired results. Proklim Bootcamp is a coaching program initiated by 3 members of the Siliwangi University PLP at the Sukahurip Village Public Housing, Settlement and Environment Department as an alternative in the coaching process in each hamlet.